THE RELATIONSHIP OF LEADERSHIP SUPERVISION WITH EMPLOYEE DISCIPLINE IN EDUCATION AND TRAINING CENTER FOR INDUSTRIAL AND TRADE COOPERATION, WEST SUMATERA PROVINCE - irsyad irsyad (Universitas Islam Negeri Sumatera Utara Medan, 2019)
This study aims to determine the leadership and supervision of employee discipline and to know whether there is a significant relationship between supervisor leadership to work discipline employees at UPTD Cooperative Training Center for Industry and Commerce of West Sumatra Province. The population is all employees of Cooperative Training Center for Industry and Commerce of West Sumatra Province. Data were analyzed by using product moment correlation formula. The results of data analysis showed that: supervisor leadership to the employees is in pretty good category, employee discipline is in pretty good category, and there is a meaningful relationship between supervisory leadership with employee discipline Cooperative Training Center for Industry and Commerce of West Sumatra Province. It means leadership oversight is one factor that affects employee discipline at Cooperative Training Center for Industry and Commerce of West Sumatra Province.